Gyroscope Implementation in Arcade Shooter Game â€œFull Metal Parabellumâ€ - Darius Andana Haris; Jeanny Pragantha; Carmello Fabrian Husen (Journal of Games, Game Art, and Gamification, 2021)
â€œFull Metal Parabellumâ€ is a three-dimensional rail shooter game for smartphone with an Android Operating System. This game was created using Unity 3D game engine for Android platform. In this game, player will have to defeat all enemies in every stages. Player can move the in-game camera and aim by moving the smartphone around. This game is tested by black box testing, alpha testing, and beta testing with a survey distributed to 30 respondents. The survey shows that Full Metal Parabellum is a fun game that easy to play, and the gyroscope feature that was implemented in this game is working as planned.